Impeded Industrial Restructuring: The Growth Penalty - D.B. Audretsch; M.A. Carree; A.J. van Stel; A.R. Thurik (Tinbergen Institute, 2000)
This paper documents that a process of industrial restructuring has been transforming the developed economies, where large corporations are accounting for less economic activity and small firms are accounting for a greatershare of economic activity. Not all countries, however, are experiencing the same shift in their industrial structures. Very little is known about the cost of resisting this restructuring process. The goal of this paper is to identifywhether there is a cost, measured in terms of forgone growth, of an impeded restructuring process. The cost is measured by linking growth rates of European countries to deviations from the optimal industrial structure. Theempirical evidence suggests that countries impeding the restructuring process pay a penalty in terms of forgone growth.
Keywords: O11; L11; 330; Industry structure; firm size distribution; entrepreneurship; economic growth